Navigating the Complexities of the European Pharmaceutical Market: Challenges and Opportunities for Big and Small Pharma Companies: regulatory landscape, market access, pricing and reimbursement, big pharma companies, small pharma companies - Nazim N Haider (North American Journal of Engineering Research, 2020)
This paper discusses the challenges faced by pharmaceutical companies operating in Europe, including navigating complex regulatory environments, evolving healthcare landscapes, and market dynamics. Large pharmaceutical companies encounter hurdles related to innovation sustainability, regulatory compliance, and pricing pressures, whereas small firms struggle with limited resources, market entry barriers, and scalability issues. Despite these challenges, both big and small pharmaceutical companies have found success in Europe by adapting to market trends, forming strategic partnerships, and prioritizing patient-centric approaches. The paper aims to provide insights into the European pharmaceutical market, explore successful drug launches, and propose a framework for success in this dynamic region.